Meta-analysis of associations between TCF7L2 polymorphisms and risk of type 2 diabetes mellitus in the Chinese population - Wang Jinjin; Hu Fulan; Feng Tianping; Zhao Jingzhi; Yin Lei; Li Linlin; Wang Yan; Wang Qian; Hu Dongsheng (BMC, 2013)
Abstract Background Associations between transcription factor 7-like 2 (TCF7L2) polymorphisms and type 2 diabetes mellitus (T2DM) have been evaluated extensively in multiple ethnic groups. TCF7L2 has emerged as the strongest T2DM susceptibility gene in Europeans, but the findings have been inconsistent in the Chinese population. The purpose of this meta-analysis was to evaluate the associations between TCF7L2 single nucleotide polymorphisms (SNPs) and T2DM risk in the Chinese population. Methods We performed searches in the PubMed, EMBASE, Cochrane, and Chinese databases (CNKI, CQVIP and Wanfang databases) for literature published from January 2007 to February 2012. We reviewed all relevant articles on TCF7L2 polymorphisms and susceptibility to T2DM in the Chinese population written in English and Chinese. Two reviewers extracted data independently using a standardized protocol, and any discrepancies were adjudicated by a third reviewer. Fixed-effects and random-effects meta-analyses were performed to pool the odds ratios (ORs). Publication bias and heterogeneity were examined. Results A total of 21 articles were confirmed to be eligible for and included in this meta-analysis: 7 (with 3942 cases and 3502 controls) concerning rs11196218 (IVS−/+4G>A), 8 (with 3377 cases and 2975 controls) concerning rs290487 (IVS3−/+C>T), and 14 (with 7902 cases and 7436 controls) concerning rs7903146 (IVS3−/+C>T). Overall, the results showed a significant association between rs7903146 and T2DM risk. The pooled ORs were 1.54 for the comparison of T and C alleles (95% CI [confidence interval]: 1.37-1.74, p = 1.47 × 10-12, I2 = 25.20%) and 1.56 for TC heterozygotes and CC homozygotes (95% CI : 1.38-1.76, p = 8.25 × 10-9, I2 = 21.00%). The rs11196218(IVS4G>A) and rs290487 (IVS3C>T) SNPs were not associated with T2DM risk. Conclusions The rs7903146 SNP of the TCF7L2 gene is associated with increased susceptibility to T2DM in the Chinese population as a whole as well as northern Chinese and southern Chinese as subgroups.